Geometrical solution to the sharkskin instability - Pol, Harshawardhan V.; Joshi, Yogesh M.; Tapadia, Prashant S.; Lele, Ashish K.; Mashelkar, Raghunath Anant (Industrial & Engineering Chemistry Research, 2007)
We study the effect of die exit divergence on the sharkskin behavior, both experimentally as well as through the use of computational fluid dynamics (CFD) simulations. Sharkskin or surface fracture is known to occur immediately after the die exit, because of the large elongational deformation that a polymer melt experiences as it exits the die. We show that the diverging taper at the die exit postpones or completely removes the occurrence of sharkskin. The corresponding CFD simulations of an equivalent K-BKZ fluid show that the taper at the die exit significantly reduces the severity of the elongational flow, thereby reducing the normal stresses as the polymer melt leaves the die. We believe that, in an extrusion operation, the provision of a diverging taper at the die exit is one of the potential measures by which sharkskin instability can be eliminated on an industrial scale.

Gelation of regenerated fibroin solution - Nagarkara, Shailesh; Lele, Ashish K.; Chassenieux, Christophe; Nicolai, Taco; Durand, Dominique (15th International Congress on Rheology/80th Annual Meeting of the Society-of-Rheology, 2008)
Silk fibroin is a high molecular weight multiblock ampiphillic protein known for its ability to form high strength fibers. It is also biocompatible; silk sutures have been traditionally used for many centuries. Recently, there has been much interest in making silk hydrogels for applications ranging from tissue engineering to controlled delivery. Fibroin gels can be formed from aqueous solutions by changing one or more state variables such as pH, temperature and ionic strength. In this work we present our investigations on the gelation of aqueous fibroin solutions derived from Bombyx Mori silk using light scattering, confocal microscopy and rheological techniques.
15th International Congress on Rheology/80th Annual Meeting of the Society-of-Rheology, Monterey, CA, AUG 03-08, 2008
Keywords: dynamic light scattering; Rheology; silk fibroin gel